(untitled) (Academia Science Repository, 2023)
This research built a Smart Electrical Muscle Stimulator (EMS) by using Raspberry Pi4, OLIMEX 328, and an EMG shield. The idea of this research is to follow the ECG and EMG of the patient while his muscle stimulation is carried on, the stimulation level will be decided according to the ECG output. Using Raspberry Pi4 gives the possibility of Bluetooth remote control and programable parameters of the EMS device.